Persistent kidney dysfunction after acute kidney injury predicts short‐term outpatient mortality. Issue 5 (10th May 2022) - Quiroga, Borja; Sanz Sainz, Marta; Santos Sánchez‐Rey, Begoña; Muñoz Ramos, Patricia; Ortiz, Alberto; Ruano, Pablo
Abstract: Background: Acute kidney injury (AKI) during hospitalisation is frequent and associated with adverse outcomes. Aims: To evaluate the association between renal function recovery after AKI and short‐term post‐discharge mortality. Methods: This is a retrospective study of all AKI episodes codified in the electronic records of a single centre in 2013 and 2014. Epidemiological data and comorbidities at baseline and laboratory values at admission and discharge were collected. Persistent kidney dysfunction after AKI was defined as a last serum creatinine equal or above 1.2‐fold over baseline level. Patients were followed for 30 days after discharge. Results: Out of 1720 evaluated patients, 1541 (89%) were analysed. Of them, 869 (56%) recovered renal function. Independent predictors of renal function recovery after AKI were lower baseline estimated glomerular filtration rate (eGFR) ( P < 0.001), higher admission eGFR ( P < 0.001) and haemoglobin ( P = 0.016), milder AKI ( P = 0.037), absence of a history of heart failure ( P < 0.001) and lower admission blood pressure ( P < 0.001). After discharge, 46 (3%) patients died in the first 30 days. Persistent kidney dysfunction was associated ( P = 0.01) with and independently predicted (odds ratio 2.6; 95% confidence interval 1.2–5.4; P = 0.01) short‐term post‐discharge mortality. Conclusions: Persistent kidney dysfunction after an AKI episode is an independent predictor of 30‐day post‐discharge mortality. This information might help select AKI patients who require closer follow up and monitoring after discharge.